Pengaruh Kegiatan Seminar terhadap Tingkat Pengetahuan Pemeriksaan Penunjang Penyakit Infeksi dan Autoimun pada Mahasiswa Kedokteran dan Mahasiswa Teknologi Laboratorium Medik: Penelitian - Ishan, Zulfa Khairunnisa; Hartungi, Florean; Astuti, Puji; Pratiwi, Sari Eka; Putri, Rifa Amalia; Imaduddin, Zaky (PT Kalbe Farma Tbk., 2026)
Introduction: Supporting examinations can aid in diagnosing infectious and autoimmune diseases. Conducting a health education seminar is essential to address the complexities of developing supporting examinations, particularly for future health professionals such as medical and medical laboratory students. This research aimed to analyze differences in knowledge levels regarding supportive examinations for infectious and autoimmune diseases before and after seminars for both programs' students. Methods: The research design was a quasi-experimental one-group pretest-posttest design with a total sample of 86 students from the University of Tanjungpura, Poltekkes Kemenkes Pontianak, and Poltekkes Aisyiyah Pontianak. Results: The Wilcoxon test revealed a statistically significant effect of the seminar (p < 0.005), as demonstrated by increased scores from pretest to posttest across all assessment items. Conclusion: There was an increase in the level of knowledge of supporting examinations before and after the seminar activities.